2016
DOI: 10.1016/j.ijnurstu.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Occupational factors associated with obesity and leisure-time physical activity among nurses: A cross sectional study

Abstract: Background and objective Adverse working conditions contribute to obesity and physical inactivity. The purpose of this study was to examine the associations of occupational factors with obesity and leisure-time physical activity among nurses. Methods This study used cross-sectional data of 394 nurses (mean age 48 years, 91% females, 61% white) randomly selected from the California Board of Registered Nursing list. Data on demographic and employment characteristics, musculoskeletal symptom comorbidity, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 47 publications
7
59
1
14
Order By: Relevance
“…Nurses are prone to lack of exercise, particularly those who engage in shift work 19) . This study showed the significant effectiveness of exercise intervention supervised by a PT who is working at the same hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are prone to lack of exercise, particularly those who engage in shift work 19) . This study showed the significant effectiveness of exercise intervention supervised by a PT who is working at the same hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A adoção desse perfil salutar pode estar associada ao fato de esses profissionais conhecerem os efeitos prejudiciais do sedentarismo e das substâncias psicoativas nos níveis biopsicossociais, que incluem: obesidade, diabetes mellitus, doenças cardiovasculares, depressão, distúrbios do sono, dependência de substâncias, entre outras (17) .…”
Section: Discussionunclassified
“…Essa condição é considerada próxima da ideal, pois, por não desenvolveram longas jornadas laborais, mantêm os níveis de alerta, diminuindo os riscos de eventos adversos, acidentes de trabalho, absenteísmo e presenteísmo, exaustão laboral e doenças de natureza mental que, por sua vez, são causas importantes de incapacidade permanente (17)(18) . Entretanto, tais aspectos negativos podem ocorrer com os 48(25,9%) enfermeiros desta amostra que indicaram duplo vínculo e que desenvolviam uma jornada semanal de trabalho média de 69,4 horas, com variação de 50 a 84 horas.…”
Section: Discussionunclassified
“…Low rates of leisure time physical activity are reported among timepoor nurses, particularly those shift-working and with home-care responsibilities (Chin, Nam, & Lee, 2016;Peplonska, Bukowska, & Sobala, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…High rates of overweight and obesity have been attributed, in part, to unhealthy eating environments and ward cultures (Nicholls, Perry, Duffield, Gallagher, & Pierce, ; Perry, Gallagher, et al., ). Low rates of leisure time physical activity are reported among time‐poor nurses, particularly those shift‐working and with home‐care responsibilities (Chin, Nam, & Lee, ; Peplonska, Bukowska, & Sobala, ).…”
Section: Introductionmentioning
confidence: 99%